Podoplanin: An emerging cancer biomarker and therapeutic target. Issue 5 (17th May 2018) - Krishnan, Harini; Rayes, Julie; Miyashita, Tomoyuki; Ishii, Genichiro; Retzbach, Edward P.; Sheehan, Stephanie A.; Takemoto, Ai; Chang, Yao‐Wen; Yoneda, Kazue; Asai, Jun; Jensen, Lasse; Chalise, Lushun; et al.
Abstract : Podoplanin (PDPN) is a transmembrane receptor glycoprotein that is upregulated on transformed cells, cancer associated fibroblasts and inflammatory macrophages that contribute to cancer progression. In particular, PDPN increases tumor cell clonal capacity, epithelial mesenchymal transition, migration, invasion, metastasis and inflammation. Antibodies, CAR‐T cells, biologics and synthetic compounds that target PDPN can inhibit cancer progression and septic inflammation in preclinical models. This review describes recent advances in how PDPN may be used as a biomarker and therapeutic target for many types of cancer, including glioma, squamous cell carcinoma, mesothelioma and melanoma. Abstract : Podoplanin (PDPN) is a transmembrane receptor glycoprotein that is upregulated on transformed cells, cancer associated fibroblasts (CAFs), and inflammatory macrophages that contribute to cancer progression. This review describes recent advances in how PDPN may be used as a biomarker and therapeutic target for many types of cancer including glioma, squamous cell carcinoma, mesothelioma, and melanoma.